Side-effects of thiamethoxam on the brain andmidgut of the africanized honeybee Apis mellifera (Hymenopptera: Apidae) - Oliveira, Regiane Alves; Roat, Thaisa Cristina; Carvalho, Stephan Malfitano; Malaspina, Osmar (Wiley, 2013)
The development of agricultural activities coincides with the increased use of pesticides to control pests, which can also be harmful to nontarget insects such as bees. Thus, the goal of this work was assess the toxic effects of thiamethoxam on newly emerged worker bees of Apis mellifera (africanized honeybee-AHB). Initially, we determined that the lethal concentration 50 (LC50) of thiamethoxam was 4.28 ng a.i./μL of diet. To determine the lethal time 50 (LT50), a survival assay was conducted using diets containing sublethal doses of thiamethoxam equal to 1/10 and 1/100 of the LC50. The group of bees exposed to 1/10 of the LC50 had a 41.2% reduction of lifespan. When AHB samples were analyzed by morphological technique we found the presence of condensed cells in the mushroom bodies and optical lobes in exposed honeybees. Through Xylidine Ponceau technique, we found cells which stained more intensely in groups exposed to thiamethoxam. The digestive and regenerative cells of the midgut from exposed bees also showed morphological and histochemical alterations, like cytoplasm vacuolization, increased apocrine secretion and increased cell elimination. Thus, intoxication with a sublethal doses of thiamethoxam can cause impairment in the brain and midgut of AHB and contribute to the honeybee lifespan reduction. © 2013 Wiley Periodicals, Inc.
Keywords: Apis mellifera; Digestive cells; Histochemistry; Morphology; Mushroom bodies; Neonicotinoid; Optical lobes; Regenerative cell; Toxicity